A Community Health Volunteer Involvement Program for Glycated Hemoglobin Reduction Among Thai Patients With Uncontrolled Type 2 Diabetes: A Mixed-Method Study - Penchan Sittipreechachan; Panan Pichayapinyo; Sunee Lagampan; Rewadee Chongsuwat (SAGE Publishing, 2022)
Background: Diabetes mellitus is increasing and a shortage exists of nurses to care for patients. Community health volunteers (CHVs) pose potential supportive networks in assisting patients to perform healthy behaviors. Aim: The study aimed to develop and investigate the effects of a CHV involvement program on reducing glycated hemoglobin (HbA 1c ) levels among Thai patients with uncontrolled type 2 diabetes. Methods: This sequential mixed-method study was conducted from January to June 2019. Sixty patients with HbA 1c exceeding 7% were recruited from 2 communities assigned as the intervention and comparison groups. Using King's General Systems Framework as a basis to develop the program, the study initially explored the perceptions of diabetes and its management among patients, family members, and CHVs. Then, a quasi-experimental study with 2 groups pretest-posttest design was conducted and compared with usual care. The intervention included educational sessions, home visits, and activities created by CHVs including a campaign, broadcasting, and health food shops. Quantitative data were collected at baseline and 20-week follow-up and analyzed by descriptive statistics, Independent t -test, and paired t -test. Results: The intervention group exhibited a lower mean HbA 1c ( p  < .001) and reported significant, improvement concerning diabetes knowledge, self-efficacy, perceived support, and behavior compared with the comparison group at the end of the study (Cohen's d  > 1.0, effect size large). Conclusion: Applying this framework to develop the program could benefit glycemic control among patients with uncontrolled diabetes residing in communities. Further studies should be conducted on a large sample to demonstrate the efficacy of the program.